The Role of Religiosity and Spiritual Meaningfullness towards Cyberbullying Behavior - Triantoro Safaria; Khoiruddin Bashori (Universitas Ahmad Dahlan, 2021)
Several previous studies have explained that cyberbullying has a negative impact on the victim. Currently, there are no research findings that examine the relationship between religiosity and spiritual meaning with cyberbullying. The current study is conducted to answer the gap of existing knowledge. The purpose of this study is to examine the relationship between religiosity and spiritual meaning with cyberbullying behavior. The research sample the students from a private university in Yogyakarta totaling 152 people (74 (49.3%) male; 76 (50.7%) female) who were taken by purposive sampling technique. Three questionnaires were used to collect the data. Regression analysis was implemented. The results of this study indicated that there is a very significant relationship between religiosity and spiritual meaningfulness with cyberbullying behavior. The implication of this research is to emphasize the role of religiosity and spiritual meaning for adolescents to prevent cyberbullying behavior.Keywords: Religiosity, spiritual meaning, and cyberbullying behavior